KINERJA KEUANGAN SEBELUM DAN SESUDAH IPO DAN PENGARUHNYA TERHADAP NILAI PERUSAHAAN PT GARUDA INDONESIA (PERSERO) TBK - Andayani, Niluh Sri; Wiksuana, IG. B.; Sedana, I.B. Panji (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.04.TAHUN 2017, 2017)
Companies that perform IPO usually will have a better performance on its benefit. The ratio of financial performance used by investors to make investment decisions and determine the firm value. The ratio of financial performance are profitability, leverage, liquidity, activity and growth of the company. Determining the differences in financial performance before and after the IPO and the effect of financial performance of firm value are the purpose of this study. Data were obtained from the financial statements of PT Garuda Indonesia in 2007-2015. The analytical tool used in this research are analysis of different test and multiple regression test. Different test research results showed that only liquidity had significant differences after the IPO. Multiple regression test showed that profitability variable has positive non significant effect to firm value, leverage has negative significant effect to  firm value, liquidity has positive significant effect to firm value and  company activities as well as growth have negative non significant effect to firm value.
Keywords: Profitability, Leverage, Liquidity, Company Activities,Growth, IPO